2020
DOI: 10.1101/2020.01.06.891127
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cerebellar Purkinje cell activity modulates aggressive behavior

Abstract: AbstractAlthough the cerebellum is traditionally associated with balance and motor function, it also plays wider roles in affective and cognitive behaviors. Evidence suggests that the cerebellar vermis may regulate aggressive behavior, though the cerebellar circuits and patterns of activity that influence aggression remain unclear. We used optogenetic methods to bidirectionally modulate the activity of spatially-delineated cerebellar Purkinje cells to evaluate the impact on agg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Further support for non-motor roles of CB stems from clinical translational studies, which have linked CB dysfunction with neurodevelopmental disorders, posttraumatic stress disorder, generalized anxiety disorder, addiction, and cognitive and emotional disturbances known as cerebellar cognitive affective syndrome 8,[10][11][12][13][14][15][16][17][18] . These findings are further corroborated by evidence from animal studies, which solidify a role for the CB in the processing of valence, reward, reward anticipation and omission [19][20][21][22][23] ; emotional learning and aggression [24][25][26][27][28][29][30][31] ; and motivation [32][33][34] .…”
Section: Introductionsupporting
confidence: 60%
“…Further support for non-motor roles of CB stems from clinical translational studies, which have linked CB dysfunction with neurodevelopmental disorders, posttraumatic stress disorder, generalized anxiety disorder, addiction, and cognitive and emotional disturbances known as cerebellar cognitive affective syndrome 8,[10][11][12][13][14][15][16][17][18] . These findings are further corroborated by evidence from animal studies, which solidify a role for the CB in the processing of valence, reward, reward anticipation and omission [19][20][21][22][23] ; emotional learning and aggression [24][25][26][27][28][29][30][31] ; and motivation [32][33][34] .…”
Section: Introductionsupporting
confidence: 60%
“…Prior evidence for a cerebellar role in organized cognition has come from lesions and correlational imaging studies ( 72 ). A wealth of recent murine studies has demonstrated a critical role for the cerebellum in multiple aspects of cognition ( 73 77 ). In this model we add social cognition to the growing list of cognitive domains dependent on cerebellar computation.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, several studies have further underscored the importance of the cerebellum in higher order function using acute, optogenetic manipulations of specific cell types. Acute activation of the cerebellar cortex disrupts hippocampal function and impairs performance in a spatial memory task [89], optogenetic activation and inhibition of Purkinje cells result in a reduction or increase in aggressive behaviors, respectively [90], and activation or inhibition of cerebellar fastigial nucleus neurons projecting to the periaqueductal gray modulate fear memories [91] (shown in Fig. 2).…”
Section: Disruptions In Cerebellar Function Lead To Social and Cognitive Deficits In Micementioning
confidence: 99%